Program Imunisasi untuk Ibu Hamil dan Anak Balita di Puskesmas Nambo - Paridah Paridah; Hartati Bahar (Lembaga Pengembangan Kinerja Dosen, 2026)
Vaccination programs are an effective preventive measure aimed at reducing the number of cases and deaths caused by vaccine-preventable diseases, especially among pregnant women and young children. This study aims to assess the implementation of the immunization program at Nambo Health Center and to identify the factors that influence community participation. This study employs a descriptive qualitative approach with a field study methodology. The research team consists of three individuals, namely one health worker, one posyandu volunteer, and one mother of a young child, selected through purposive sampling. Data collection was carried out through in-depth interviews, observations, and documentation. The validity of the data was obtained through triangulation of sources and methods, while the data analysis was conducted interactively through stages of data reduction, data presentation, and the drawing and verification of conclusions. The research results indicate that the implementation of the immunization program has followed the proper procedures, but the level of community participation is still influenced by low parental knowledge, concerns about vaccine side effects, and insufficient counseling and family support. This study indicates that improving the quality of health education, strengthening the role of posyandu volunteers, and optimizing communication between health workers and the community are necessary to increase immunization coverage. This finding is expected to serve as input for health centers and policymakers in developing more effective health promotion strategies to enhance the success of immunization programs.